Hydrocarbon source rock potential of the Early Permian rocks in the Potwar Basin, Salt Range, Pakistan - Ahmad, Faizan; Ahmad, Sajjad; Khan, Suleman; Fu, Qi; Jan, Irfan U.; Khan, Rafiq Ali; gul, Shehla; Alizai, Fahad Ali (Journal of Himalayan Earth Sciences, 2019)
In this paper the hydrocarbon source rock potential of the Early Permian strata of the Choa-Khewra Road Section in eastern Salt Range and the Zaluch Nala Section in western Salt Range, Potwar Basin, Pakistan is presented. The six outcrop samples of organic clays from the Tobra and Dandot Formations from eastern Salt range while Warchha and Sardhai Formations from the Zaluch Nala sections were collected for the Total Organic Carbon (TOC) and Rock Eval Pyrolysis analyses. Various geochemical cross plots were constructed using the total organic carbon and pyrolysis values of the analyzed rock samples to know the qualitative assessment of organic matter and presence of any indigenous or migrated hydrocarbons. Our result shows that the Tobra Formation is thermally mature with 0.55 % and 0.83 % TOC hence Type III kerogen with a tendency to generate indigenous hydrocarbons. The Dandot Formation is thermally immature Type III kerogen, with 0.78 % TOC that can generate indigenous hydrocarbons. The Warchha and Sardhai formations both are thermally immature Type III kerogen and a 0.73 %; 1.05 % and 1 % respectively, with an indigenous hydrocarbons generation potential. The XRD results shows that the percentage of clay minerals i.e. ductile minerals are less than the brittle minerals i.e. Quartz etc. Brittleness Index for the Tobra, Dandot and Warchha Formations shows brittle nature and are suitable for hydraulic fracturing while the Sardhai formation shows less brittle material and considered suitable for fracking